2017
DOI: 10.1590/s1679-45082017ao3862
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in patients admitted to clinical units at university hospital: post-discharge evaluation rated by telephone

Abstract: Objective To characterize hypertensive patients after admission to hospital considering the current status, compliance to treatment, habits and lifestyle, and knowledge and beliefs about the disease.Methods This was an exploratory study with 265 hypertensive patients admitted to a medical inpatients unit of a university hospital. Data were collected in an interview over the telephone. The level of significance was set as p<0.05.Results It was found that 32% of hypertensive patients had died. One hundred patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…A prática regular de atividade física é importante ferramenta na manutenção dos níveis pressóricos e integra o tratamento da hipertensão arterial sistêmica. Em pesquisa que caracterizou pessoas hipertensas quanto à condição e adesão ao tratamento da doença, após internação hospitalar, evidenciou que, além de importante índice de mortalidade (32%), multiplicidade de fatores, como o estilo de vida sedentário, comprometeu o adequado controle da doença (14) .…”
Section: Discussionunclassified
“…A prática regular de atividade física é importante ferramenta na manutenção dos níveis pressóricos e integra o tratamento da hipertensão arterial sistêmica. Em pesquisa que caracterizou pessoas hipertensas quanto à condição e adesão ao tratamento da doença, após internação hospitalar, evidenciou que, além de importante índice de mortalidade (32%), multiplicidade de fatores, como o estilo de vida sedentário, comprometeu o adequado controle da doença (14) .…”
Section: Discussionunclassified
“…(17) Este aconteceu de acordo como método de Design Instrucional Contextualizado (DIC), que é composto de cinco fases: análise, design, desenvolvimento, implementação e avaliação. (18,19) 1) Análise: Reconhecida a baixa adesão ao tratamento anti-hipertensivo (3,20) e conforme os preceitos da TCP, que direciona intervenções para motivar a mudança e/ou fortalecimento de atitudes, normas socias e controle percebido com base nas crenças primárias que guiam a performance do comportamento, foi realizado estudo para analisar crenças dos indivíduos com HAS em relação à tomada dos anti--hipertensivos. (21) Participaram desta etapa de levantamento de crenças 28 pessoas em uso contínuo de anti-hipertensivos, em acompanhamento ambulatorial.…”
Section: Métodosunclassified
“…(1) É uma das causas mais importantes de mortalidade prematura no mundo, e também um dos fatores de risco mais evitáveis de doenças cardiovasculares, que pode ser facilmente detectada e efetivamente tratada com medicamentos de baixo custo e mudanças no estilo de vida. (1,2) Entre os desafios remanescentes do tratamento medicamentoso da HAS encontram-se a baixa adesão ao tratamento e o descontrole dos níveis de pressão arterial (PA), (3) que reverberam em complicações da doença e em ônus socioeconômico pessoal, familiar e para o setor da saúde. (4) Supõe-se que o aumento da participação do paciente no manejo do comportamento de tomar os comprimidos anti--hipertensivos prescritos seja uma estratégia viável, facilitada por novas tecnologias de intervenção, (5) e um caminho promissor, ao reduzir o foco nas medidas reativas e estimular medidas proativas, com o propósito de apoiar o autogerenciamento da doença pelo indivíduo, com consequente redução da não adesão.…”
Section: Introductionunclassified
“…Such fact occurs because it is a long-term treatment, with the presence of adverse effects, considerable cost and, sometimes, unpleasant, which results in lack of adherence. 1 Thus, it is important to develop motivating, theory-based strategies, to strengthen and encourage the taking of antihypertensives. 2 The Theory of Planned Behavior (TPB) assumes that human behavior is predicted by intention (motivation) and influenced by three psychosocial determinants and their respective beliefs: attitude, formed by behavioral beliefs, likely outcomes of behavior and evaluations of these outcomes by individuals; subjective norm, formed by normative beliefs about the opinion of significant people and the motivation to meet these expectations; and perceived behavioral control, inherent to control beliefs about the presence of factors that may facilitate or impede behavior performance.…”
Section: Introductionmentioning
confidence: 99%
“…17 In Brazil, no studies have been identified on the development of communication and persuasive messages directed at the behavior "use of oral antihypertensives", despite the evidence of low adherence of people with SAH to treatment, which implies unfavorable outcomes in maintaining health and quality of life. 1 Considering the problem of SAH for public health and the need to incorporate light technologies as adjuvant strategies to enhance therapeutic adherence and, consequently, reduce complications and the prevalence of the disease, audiovisual resources with persuasive content structured based on the beliefs, preferences and understanding of the therapy instituted by this population should be the focus of health actions that go beyond traditional intervention strategies.…”
Section: Introductionmentioning
confidence: 99%